Influence of service quality and company image on electronic word-of-mouth (eWOM) through customer satisfaction among train passengers at PT. Indonesian Railways (Persero) Regional Division II West Sumatra. - Rahma Lisya, Sri; Thamrin, Thamrin (Marketing Management Studies, 2024)
This study aims to see the effect of service quality and corporate image on EWOM through consumer satisfaction at PT. KAI Drive SUMBAR. The population of this study is people who have used the services of PT. KAI Drive II SUMBAR in the last 6 months. The number of samples used in this study were 130 respondents. Data was collected by distributing questionnaires online via Google from and data processing was carried out using the SmartPLS software. The results of this study indicate that (1) Service quality has a positive and significant effect on EWOM (2) Service quality has a positive and significant effect on customer satisfaction (3) Corporate image has a positive and significant effect on EWOM (4) Corporate image has a negative effect on customer satisfaction ( 5) customer satisfaction has a negative effect on EWOM (6) Service quality has a negative effect on EWOM through customer satisfaction (7) Corporate image has a positive and significant effect on EWOM through customer satisfaction.